Regional Integration and Trade in Africa - Ncube, Mthuli, 1963-; Faye, Issa, 1972-; Verdier-Chouchane, Audrey, 1973- (UK : Palgrave Macmillan, 2015)
"Regional integration has been adopted by many African governments as a response to difficulties facing national markets in landlocked countries. However, despite the aspiring targets they have experienced setbacks due to poor implementation. This book reviews the current trends, challenges and potential benefits of regional integration and trade in Africa, in a context of rising interest and momentum among African leaders on the topic.This study explores the many facets of regional trade, its implementation gaps and positive effects through empirical studies covering various African sub-regions and using different theoretical approaches. It analyses trade performance against full potential, its mitigated impact on the competitiveness, industrialization and economic diversification of African countries as well as the much debated effect of monetary unions on regional trade in the region. It provides valuable policy recommendations aimed at stimulating the debate among the government, private sector and development community on the ways to promote regional trade for Africa's economic development.Regional Integration and Trade in Africa examines various aspects of regional integration and trade in Africa, and will be of interest to scholars, students, researchers, policy-makers, and professionals"--
Machine generated contents note: -- Overview Chapter: Understanding Africa's Regional Trade; Mthuli Nucbe, Issa Faye and Audrey Verdier-ChouchanePART I: INTRA-AFRICAN TRADE PERFORMANCE AND REGIONAL INTEGRATION1. Competitiveness and Integration through Trade in CEMAC Countries: Comparative Advantage and Contribution to the Trade Balance; Jospeh Parfait Owoundi2. Economic integration, Trade Facilitation and Agricultural Exports Performance in ECOWAS Sub-Region; Wumi Olayiwola, Evans Osabuohien, Henry Okodua and Oluyomi Ola-David3. The Impact of Trade Liberalization on Export Growth and Import Growth in Sub-Saharan Africa; Lanre KassimPART II: MEASURING TRADE POTENTIAL: THE GRAVITY MODEL APPROACH4. Market Integration in the ECCAS Sub-Region; De;sire; Avom and Mouhamed Mbouandi Njikam5. Regional Integration and Trade in Sub-Saharan Africa, 1993-2010: An Augmented Gravity Model; Edris SeidPART III: INDUSTRIALIZATION STRATEGY AND THE ISSUE OF DEINDUSTRIALIZATION6. Malawi's Trade Policies, Market Structure, and Manufacturing Performance, 1967-2002; Hopestone Kayiska Chavula 7. Impact of South-South and North-South Trade on Industrialization in Africa; Henri Atangana Ondoa and Tabi Henri NgoaPART IV: IMPACT OF CURRENCY UNION ON TRADE8. Impact of Monetary Unions on Trade: The Case of WAEMU; Ibrahima Camara9. Trade Agreements and Flows in ECOWAS: Is a Single Currency the Determining Factor?; Benjamin Ndong and Sokhana Diarra Mboup10. A DSGE Model of Trade and Risk-sharing Effects of Currency Union on Economic Integration of the CFA Zone; Thierry Kame BabillaConcluding Chapter: Enhancing Intra-African Trade through Regional Integration; Mthuli Ncube, Issa Faye and Audrey Verdier-Chouchane.
Includes bibliographical references and index.
Keywords: Economic integration; Africa -- Commercial policy; Africa -- Commerce; Africa -- Economic integration; Africa -- Foreign economic relations